TERT promoter mutations are a major indicator of recurrence and death due to papillary thyroid carcinomas. (8th February 2016) - Bullock, Martyn; Ren, Yan; O'Neill, Christine; Gill, Anthony; Aniss, Adam; Sywak, Mark; Sidhu, Stan; Delbridge, Leigh; Learoyd, Diana; de Vathaire, Florent; Robinson, Bruce G.; Clifton‐Bligh, Roderick J.
Summary: Context: TERT promoter mutations have been associated with adverse prognosis in papillary thyroid carcinomas (PTCs). Objective: We investigated the association between TERT promoter mutations and survival from PTC. Design: Retrospective observational cohort study. Patients: Eighty consecutive patients with PTC who underwent surgery between 1990 and 2003. Measurements: TERT promoter was genotyped in DNA from 80 archival PTCs by Sanger sequencing. Median follow‐up was 106 months (range 1–270). Outcomes analysis was stratified according to disease and overall survival status. For each parameter, relative risk (RR) adjusted for age at first surgery and gender was estimated. Both univariate and multivariate analyses were performed using logistic regression, Kaplan–Meier survival analysis and Cox regression models. Results: PTCs from 11 patients (14%) contained either C228T or C250T TERT promoter mutation. TERT mutations were significantly associated with adverse prognostic features such as older age ( P = 0·002), male gender ( P = 0·01) and Stage IV disease ( P = 0·03). Four patients died from PTC during follow‐up: 3 patients with TERT mutations (27%) and one without (1·5%). Disease‐related mortality rate with or without TERT mutations was 33·7 vs 1·6 per 1000 patient‐years respectively, that is 10 (95% CI = 1·0–104·1, P = 0·05) fold higher, after adjustment for age at first surgery and gender. The combination of TERT promoter mutation and BRAF V 600E significantly increased disease‐related death risk ( P = 0·002). TERT mutations increased expression of a reporter gene in thyroid cells containing BRAF V 600E . Conclusions: TERT promoter mutations are a major indicator of death due to PTCs. Conversely, absence of TERT mutations portends better survival.